Neuroprotective mechanisms of Buyang Huanwu decoction in ischemic stroke - Qin, Yuanyuan; Hu, Shiliang; Mawen, Shiman; Pan, Shanyao; Huai, Yaping; Liang, Guoqiang; Chen, Ting; Zhao, Feiyan; Dong, Hongli; Yao, Xuyi; Wu, Xue; Lv, Zhigang; et al. (Frontiers in Pharmacology, 2025)
Ischemic stroke (IS) continues to be a major contributor to global mortality and long - term disability. Buyang Huanwu Decoction (BHD), a traditional Chinese medicine formula, has shown effectiveness in reducing brain injury and promoting post - stroke recovery through experimental researches and clinical trials. The neuroprotective mechanisms of BHD against cerebral ischemic injury involve multiple pathways, such as suppression of inflammation, reduction of oxidative stress, inhibition of apoptosis, regulation of autophagy, and enhancement of mitochondrial function. Moreover, BHD presents therapeutic potential by boosting neuroplasticity, enhancing angiogenesis, reducing excitotoxicity, optimizing brain energy metabolism, and regulating gut microbiota. Considering the current scarce effective treatments for IS, exploring BHD’s therapeutic potential and its mechanism holds substantial clinical significance. This review systematically organizes recent research advancements on BHD’s application in IS management and its underlying mechanisms, providing useful insights for future research and clinical practice.